1993
DOI: 10.1016/s0006-3495(93)81330-4
|View full text |Cite
|
Sign up to set email alerts
|

An x-ray absorption near edge structure spectroscopy study of metal coordination in Co(II)-substituted Carcinus maenas hemocyanin

Abstract: High-resolution x-ray absorption near edge structure spectroscopy was used to characterize the metal sites in three different cobalt-substituted derivatives of Carcinus maenas hemocyanin (Hc), including a mononuclear cobalt, a dinuclear cobalt and a copper-cobalt hybrid derivative. Co(II) model complexes with structures exemplifying octahedral, trigonal bipyramidal, pseudo-tetrahedral, and square planar geometries were also studied. The results provide structural information about the metal binding site(s) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…The feature A at the absorption edge is originated by the tetragonal distortion in the metal cluster, and its magnitude and position depend on the degree of the distortion. Non‐negligible presence of this feature has been suggested to be an indicator of a fivefold square‐pyramidal coordination . Also, the feature B reflects essentially the difference in the axial geometry of the Cu clusters.…”
Section: Resultsmentioning
confidence: 99%
“…The feature A at the absorption edge is originated by the tetragonal distortion in the metal cluster, and its magnitude and position depend on the degree of the distortion. Non‐negligible presence of this feature has been suggested to be an indicator of a fivefold square‐pyramidal coordination . Also, the feature B reflects essentially the difference in the axial geometry of the Cu clusters.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Hc in solution, only the standard Hc structure b fits the experimental data reasonably well (F Ï­ 1.23), whereas structures with long apical distances (structures c and d; F Ï­ 2.77 and 2.30, respectively) are rejected. Also in structures a and d, where the tetrahedral character of the transition metal coordination increases due to the decreasing of colinearity of MS pathways, extended spectral changes are expected (Bianconi et al, 1988;Della Longa et al, 1993) and are actually observed in the calculations (F Ï­ 1.51 and 1.42, respectively), so the reproduction of the experimental spectrum is worse. The fitting does not improve by using a linear combination of more than one structure (a Ï© b in Table III, F Ï­ 1.25, with a negligible percentage of structure a); hence, the only conclusion is that Hc has equivalent pyramidal copper sites with a short apical distance (as probed by EXAFS) and the dioxygen parallel to the pyramid base.…”
Section: Interpretation Of the Differences Between Tyrosinase Andmentioning
confidence: 90%
“…This change results in the blue color developed by type 3 copper proteins upon oxygenation. The active sites of phenoloxidase and hemocyanins with oxygen bound to the copper atoms exhibit similar spectroscopic properties with respect to UV-resonance Raman, X-ray absorption and UV/VIS spectroscopy (Eickman et al, 1978;Himmelwright et al, 1980;Pate et al, 1989;Della Longa et al, 1993;Karlin, 1993;Solomon et al, 1994Solomon et al, , 1996Spritz et al, 1997;Itoh et al, 2001;Metz and Solomon, 2001):…”
Section: Active Sitementioning
confidence: 99%